Psychometric Properties of the Sport Performance Psychological Inventory in qualified Peruvian athletes - Cortez-Saldarriaga, M. (2022)
To measure athlete's success and his sports performance, it is required to quantify the maximum performance developed during seasons of trainings and championships; using a valid, reliable, and adapted to peruvian context instrument. However, caution is urged when considering there is no psychometric evidence to support the use of any scale related to peruvian high performance athletes' sample. The current study was designed to evaluate the psychometric properties of the Sports Performance Psychological Inventory (IPED) in the mentioned sample. Method: Participated 255 peruvian athletes with ages between 14 and 38 years (N:23; SD: 4.29); who actively represents the country and in sports modalities affiliated with the Peruvian Sports Institute (IPD). For the collection of information, a sociodemographic record, Sports Performance Psychological Inventory (IPED) and the Mental Toughness Questionnaire (MTQ) were used. Results: IPED model demonstrated, that the seven-dimensional model had an acceptable fit (SBx2 = 2243.096 / df = 798; CFI=. 955; SRMR=. 095; RMSEA=. 084 [IC90%:. 080 -. 069] and reliability analyses revealed high internal consistency (ω =. 841 > ω =. 754). In addition, scores correlated positively between IPP and MTQ dimensions (AC=. 678; CAN=. 557; CAT=. 457; CVI=. 328; NM=. 425; CAP=. 641; CAC=. 662) and Control (AC=. 558; CAN=. 733; CAT=. 682; CVI=. 171; NM=. 272; CAP=. 432; CAC=. 563) Conclusion: The IPED provides adequate evidence of validity and reliability to measure sports performance